Elaiophores in Gomesa bifolia (Sims) M.W. Chase & N.H. Williams (Oncidiinae: Cymbidieae: Orchidaceae): Structure and oil secretion - Aliscioni, Sandra Silvina (2009)
Background and Aims Oils are an unusual floral reward in Orchidaceae, being produced by specialized glands called elaiophores. Such glands have been described in subtribe Oncidiinae for a few species. The aims of the present study were to identify the presence of elaiophores in Gomesa bifolia, to study their structure and to understand how the oil is secreted. Additionally, elaiophores of G. bifolia were compared with those of related taxa within the Oncidiinae. Methods Elaiophores were identified using Sudan III. Their structure was examined by using light, scanning electron and transmission electron microscopy. Key Results Secretion of oils was from the tips of callus protrusions. The secretory cells each had a large, centrally located nucleus, highly dense cytoplasm, abundant plastids containing lipid globules associated with starch grains, numerous mitochondria, an extensive system of rough and smooth endoplasmatic reticulum, and electron-dense dictyosomes. The outer tangential walls were thick, with a loose cellulose matrix and a few, sparsely distributed inconspicuous cavities. Electron-dense structures were observed in the cell wall and formed a lipid layer that covered the cuticle of the epidermal cells. The cuticle as viewed under the scanning electron microscope was irregularly rugose. Conclusions The elaiophores of G. bifolia are of the epithelial type. The general structure of the secretory cells resembles that described for other species of Oncidiinae, but some unique features were encountered for this species. The oil appears to pass through the outer tangential wall and the cuticle, covering the latter without forming cuticular blisters.